Acquired cystic disease‐associated renal cell carcinoma with a focal sarcomatoid component: Report of a case showing more pronounced polysomy of chromosomes 3 and 16 in the sarcomatoid component. (26th November 2014) - Tajima, Shogo; Waki, Michihiko; Doi, Wataru; Hayashi, Kazumasa; Takenaka, Syunsuke; Fukaya, Yoshie; Kimura, Ryosuke
<x xml:space="preserve">Abstract</x> Acquired cystic disease (ACD)‐associated renal cell carcinoma (RCC) has recently been established. Herein we report the sixth case of ACD‐associated RCC with a sarcomatoid change. The patient was a 77‐year‐old man who regularly underwent hemodialysis for 14 years due to chronic renal failure resulting from IgA nephropathy. On computed tomography, a large right RCC was observed with contrast enhancement in the arterial phase. A nodular protrusion into the perirenal fat was detected. Right nephrectomy was performed under laparoscopy. Surgically resected specimens revealed a tan‐to‐yellow tumor (95 × 75 × 55 mm) with a whitish nodule (20 × 15 × 15 mm) invading into the perirenal fat. Histopathologically, the large carcinoma component of the tumor displayed a cribriform or microcystic growth pattern with deposition of oxalate crystals. The whitish nodule corresponded to the sarcomatoid component, and the spindled and pleomorphic tumor cells showed diffuse positivity of p53 on immunohistochemistry. Fluorescence in situ hybridization revealed trisomy of chromosomes 3 and 16 in the carcinoma component, as was expected from the literature. In addition, increased polysomy of these chromosomes was also observed in the sarcomatoid component. This finding may be related to the development of the sarcomatoid component along with the TP53 mutation.